Light Carries On - Crivilare, Gabriella (Hollins Digital Commons, 2020)
Light Carries On, a young adult fantasy novel, comprises the creative segment of the thesis. Valo, a member of a harpy-like species, serves as a musher for his tundra-bound, flightless society. When his mate falls ill with a deadly disease, he must race against time to seek out and deliver a cure. The manuscript reimagines the Great Race of Mercy—the relay of diphtheria antitoxin from Nenana, Alaska to Nome by sled teams in 1925—with a “Cinderella” inspired element. The accompanying critical paper, “A Fairy Tale, a Race, and an Enchanted Place: The Road to Enlightenment in Light Carries On,” discusses the manuscript in comparison to East, The Cry of the Icemark, and Tess of the Road. It also provides a topographical analysis of the main character’s journey and an examination of how the author’s writing process adheres to the home-away-home format of a circular narrative.